PERSPEKTIF MAQÂ?ID SYARI’AH TERHADAP SISTEM SADOH BURUH TANI DALAM TRADISI NGERAMPEK DI DESA KURIPAN SELATAN KECAMATAN KURIPAN KABUPATEN LOMBOK BARAT - Fauzi, Muhammad (STIS Darussalam Bermi, 2022)
The form of muamalah transaction that is often carried out by the Sasak tribe community, especially the people of South Kuripan Village, Kuripan West Lombok is the tradition of the ngerampek sadoh (Wage) system, this tradition of the ngerampek sadoh (Wage) system has been going on for a long time, and has even become a tradition that has been passed down from generation to generation until now. This. The discussion in this research concerns the sadoh system of farm workers in the